Vloga svetovne gospodarske krize pri spreminjanju razmerij moči v nacionalnih političnih sistemih - Fink-Hafner, Danica (Teorija in praksa, 2011)
This article analyses several changing relationships among the key political players in national political systems (with a case study focus on Slovenia): namely the relationships between the branches of power (primarily between the legislative and executive) as well as among the key political decision-makers and civil society. The main thesis advanced is that power relations are changing in favour of the executive and at the expense of the legislative and consultative politics - especially social partnership. These trends are further enhanced by the processes of globalisation and European integration. The current economic and financial crisis is strengthening this trend whilst at the same time allowing for more radical changes to take place in a relatively short time-span.
Keywords: Globalizacija; Globalization; Political systems; Politični sistemi; Kapitalizem; Capitalism; Economic crises; Ekonomske krize